Isolation and Characterization of Mouse Monoclonal Antibodies That Neutralize SARS-CoV-2 and Its Variants of Concern Alpha, Beta, Gamma and Delta by Binding Conformational Epitopes of Glycosylated RBD With High Potency - Mariotti, Sabrina; Capocefalo, Antonio; Chiantore, Maria Vincenza; Iacobino, Angelo; Teloni, Raffaela; De Angelis, Maria Laura; Gallinaro, Alessandra; Pirillo, Maria Franca; Borghi, Martina; Canitano, Andrea; Michelini, Zuleika; Baggieri, Melissa; et al. (Frontiers in Immunology, 2021)
Antibodies targeting Receptor Binding Domain (RBD) of SARS-CoV-2 have been suggested to account for the majority of neutralizing activity in COVID-19 convalescent sera and several neutralizing antibodies (nAbs) have been isolated, characterized and proposed as emergency therapeutics in the form of monoclonal antibodies (mAbs). However, SARS-CoV-2 variants are rapidly spreading worldwide from the sites of initial identification. The variants of concern (VOC) B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma) and B.1.167.2 (Delta) showed mutations in the SARS-CoV-2 spike protein potentially able to cause escape from nAb responses with a consequent reduction of efficacy of vaccines and mAbs-based therapy. We produced the recombinant RBD (rRBD) of SARS-CoV-2 spike glycoprotein from the Wuhan-Hu 1 reference sequence in a mammalian system, for mice immunization to isolate new mAbs with neutralizing activity. Here we describe four mAbs that were able to bind the rRBD in Enzyme-Linked Immunosorbent Assay and the transmembrane full-length spike protein expressed in HEK293T cells by flow cytometry assay. Moreover, the mAbs recognized the RBD in supernatants of SARS-CoV-2 infected VERO E6 cells by Western Blot under non-reducing condition or in supernatants of cells infected with lentivirus pseudotyped for spike protein, by immunoprecipitation assay. Three out of four mAbs lost their binding efficiency to completely N-deglycosylated rRBD and none was able to bind the same recombinant protein expressed in Escherichia coli, suggesting that the epitopes recognized by three mAbs are generated by the conformational structure of the glycosylated native protein. Of particular relevance, three mAbs were able to inhibit Wuhan SARS-CoV-2 infection of VERO E6 cells in a plaque-reduction neutralization test and the Wuhan SARS-CoV-2 as well as the Alpha, Beta, Gamma and Delta VOC in a pseudoviruses-based neutralization test. These mAbs represent important additional tools for diagnosis and therapy of COVID-19 and may contribute to the understanding of the functional structure of SARS-CoV-2 RBD.